EKSLUSIVITAS GELAR HABIB: TRADISI, KONTROVERSI DAN SOLUSI AL-QUR’AN BAGI UMAT - Masyhadi, Ahmad Aziz; Fahimah, Siti; Tasmuji (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
Currently, the debate surrounding the lineage of the Habib is becoming increasingly widespread. However, in recent developments, this issue has turned into a platform for mutual hatred. Therefore, a middle ground is needed to prevent the discourse on lineage from spiraling out of control. The Qur’an can serve as a solution to strengthen the unity of the Muslim community. Using a literature study approach and critical analysis of Qur'anic arguments, this research investigates the exclusivity of the Habib title. This study offers a Qur'anic solution to address this phenomenon, particularly in fostering equality, Islamic brotherhood (ukhuwah Islamiyah), and social justice. It also aims to provide a more objective perspective on the position and role of the Habib within Muslim society and to develop a more inclusive approach to building communal harmony. In this study, the Qur’an, as the holy scripture, provides guidance on morality and brotherhood. It teaches that the most honorable person in the sight of Allah is the one with the highest level of piety (taqwa). This verse is relevant to all of humanity, regardless of ethnicity or lineage. The Qur’an emphasizes that what truly matters is piety, not social status. Piety arises from a transcendental moral awareness. The focus of Muslims should be on self-improvement rather than boasting about lineage, which only generates controversy without any real benefit.